ACCLIMATIZATION/TEST ADAPTATION OF ABACA BANANA (Musa textitis) SEEDLING DERIVED FROM TISSUE CULTURE - Mohammad Ansar; Ramal Yusuf (Tadulako University, 2014)
This study aims to determine a good growing medium that is capable of supporting the early seedling growth of abaca banana seedling during the period of acclimatization that taken from tissue culture. It has been carried out in a greenhouse located in the Kalukubula Village Sub District Sigi-Biromaru District Sigi Central Sulawesi Province. In this study used a randomized block design (RBD) with three replications. The treatment consists of 6 (six) 'type and composition of growth media were: M1 = soil, M2 = soil + Casting (1: 1), M3 = soil + Bokashi (1: 1), M4 = soil+ rice husk (1.1), M5 = soil + rice Husk Charcoal (1: 1) and M6 = soil + Sawdust (1: 1). The results showed that different types of media can provide different seedling growth which the soil media + rice husk can provide growth of abaca plant higher than other growing media treatments, characterized by the increase in plant height, number of leaves, total plant dry weight, total leaf per plant, net assimilation rate and the rate of growth, Key Words: Acclimatization, Abaca Banana, Growth